Diversity of Color, Infrared Spectra, and Phenolic Profile Correlation in Citrus Fruit Peels - Rosa Zapata; Lorena Martínez-Zamora; Francisco Artés-Hernández (Biology and Life Sciences Forum)
Citrus waste is a source of phytochemicals with extensive health properties, mainly diglycosylated flavonoids. In this experiment, the characterization of dried peels from three main citrus species, lemon (Citrus limon), orange (Citrus sinensis), and grapefruit (Citrus paradisi), was performed using various analytical techniques. The FTIR spectra of each species show the characteristic bands of C=O stretching and O-H stretching and bending, and the PCA shows discrimination between species based on their chemical nature. The TPC determined by UV-vis spectroscopy was found to be higher for grapefruit peel by 12.4% and 38.9% compared to lemon and orange, which coincides with the individual flavonoid content obtained by HPLC-MS/MS. Meanwhile, full-scan HPLC-MS confirmed a wider variety of phytochemicals in lemon peel.